2020
DOI: 10.1016/j.jhepr.2020.100080
|View full text |Cite
|
Sign up to set email alerts
|

Circulating levels of soluble urokinase plasminogen activator receptor predict outcome after resection of biliary tract cancer

Abstract: suPAR pre-OP Log-rank = 8.003 p = 0.005 2,500 Overall survival Circulating suPAR Biliary Tract Cancer (BTC) Highlights Biliary tract cancer is associated with poor outcomes and increasing incidence. Surgical resection is the only potentially curative treatment option for patients with biliary tract cancer. The identification of ideal surgical candidates has remained challenging. Circulating suPAR represents a novel diagnostic and prognostic biomarker in resectable patients. SuPAR might be useful to identify pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
18
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 46 publications
2
18
0
Order By: Relevance
“…Our data are in line with previous publications showing elevated suPAR serum levels in manifold cancers. Just recently, we demonstrated that concentrations of suPAR are elevated in patients with cholangiocellular carcinoma (CCA) [18] as well as in patients with pancreatic ductal adenocarcinoma (PDAC) [34] or colorectal cancer (CRC) [20]. Notably, serum concentrations of suPAR in our cohort of patients with NET are numerically very similar to those found in CCA, PDAC and CRC.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…Our data are in line with previous publications showing elevated suPAR serum levels in manifold cancers. Just recently, we demonstrated that concentrations of suPAR are elevated in patients with cholangiocellular carcinoma (CCA) [18] as well as in patients with pancreatic ductal adenocarcinoma (PDAC) [34] or colorectal cancer (CRC) [20]. Notably, serum concentrations of suPAR in our cohort of patients with NET are numerically very similar to those found in CCA, PDAC and CRC.…”
Section: Discussionsupporting
confidence: 70%
“…suPAR was identified as a biomarker in patients with inflammatory and infectious diseases [ 13 , 14 , 15 , 16 ]. Moreover, a prognostic role for suPAR serum levels has been demonstrated in different cancers including pancreatic, cholangiocellular and colorectal malignancies [ 17 , 18 , 19 , 20 ]. However, in NET no data on a potential role of circulating suPAR as a biomarker for prediction of patients’ prognosis or response to therapies have been reported so far.…”
Section: Introductionmentioning
confidence: 99%
“…expressed on epithelial and immune cells ( 9 ). Circulating suPAR has recently been associated with inflammatory diseases and several cancer entities ( 10 15 ). During systemic inflammation, an increased shedding of uPAR on circulating neutrophils has been reported as a source of elevated suPAR levels ( 16 ).…”
Section: Introductionmentioning
confidence: 99%
“…Despite many different preinterventional stratification algorithms, such as the ART or SNACOR, optimal patient selection has remained challenging 6,8 . Soluble urokinase plasminogen activator receptor (suPAR) has been established as a promising novel biomarker reflecting the tumor biology in terms of grading or prognosis and allows us to guide preoperative treatment decisions regarding patients' outcomes in manifold cancers 9,10 . In the present study, we aimed at evaluating serum concentrations of suPAR as predictive and/or prognostic markers for patients undergoing TACE for primary and secondary liver cancer, independent of the disease etiology.…”
Section: Introductionmentioning
confidence: 99%